The space between the stars - Corlett, Anne (Berkley, 2017)
"All Jamie Allenby ever wanted was space. Even though she wasn't forced to emigrate from Earth, she willingly left the overpopulated, claustrophobic planet. And when a long relationship devolved into silence and suffocating sadness, she found work on a frontier world on the edges of civilization. Then the virus hit ... Now Jamie finds herself dreadfully alone, with all that's left of the dead. Until a garbled message from Earth gives her hope that someone from her past might still be alive. Soon Jamie finds other survivors, and their ragtag group will travel through the vast reaches of space, drawn to the promise of a new beginning on Earth. But their dream will pit them against those desperately clinging to the old ways. And Jamie's own journey home will help her close the distance between who she has become and who she is meant to be . . ."--